Success Analysis of Hospital Management Information System Using MMUST and IT Balanced Scorecard (Case Study of Bhakti Husada General Hospital Banyuwangi) - Vivi Sefrinta Izza Afkarina; Rudi Wibowo; Saiful Bukhori (Health Notions, 2021)
The management information system acts as an information manager for organizational management, users as data processors, and organizational leaders as those who carry out the control mechanism. Currently HMIS at Bhakti Husada General Hosiptal is in the development stage in order to realize the ideal HMIS. MMUST is a model for assessing system success in mandatory environments and IT Balanced Scorecard used to measure success organizational performance and consider internal processes. This type of research is quantitative with cross sectional. Data from 45 HMIS users who were selected using disproportionate stratified sampling were analyzed using the SEM-PLS technique. The results of the MMUST analysis show that the variable condition of the facility affects attitudes and attitudes affect the overall quality in supporting the success of HMIS. The results of the IT Balanced Scorecard analysis show that the performance of HMIS RSU Bhakti Husada is categorized as good. Bhakti Husada General Hospital need to consider budget allocation for the HMIS module integration development by collaborating with several developers so that they can accelerate HMIS development, provide user authorization to hospital employees according to their main tasks and functions, and developing HMIS capable of implementing electronic medical records.Keywords: HMIS; MMUST; IT balanced scorecard; HMIS success